Identification Of The Innovation Practices Factors In Pedagogy In High School Education - Radouane Aboufirass; Said Lotfi; Mohammed Talbi (Journal of Information Technology Management)
Research in ​​educational innovation has generally focused on teaching practices. Innovation in our society carries many identities. In the collective imagination, it refers to our own representation of what is new. In our research work, we have focused on identifying the factors of innovation in the field of qualifying secondary education. We used a questionnaire of 78 items, structured in 5 areas: the conditions, the moments, the reasons, the domains, and the objects of experimentation of the new actions in teaching-learning. This questionnaire is administered to a sample of 149 teachers. We proceeded by a descriptive and exploratory research of mixed qualitative and quantitative type) The results of which showed the existence of personal factors and those which are in relation to the context and the working conditions in educational establishments, and which are points of reflection on the logic of school innovation. We can deduce that an analysis of the relationships that teachers have with innovation opens heuristic perspectives in terms of research and training in education.